1979
DOI: 10.1177/009539977901100304
|View full text |Cite
|
Sign up to set email alerts
|

Scarcity and Environmental Stress in Public organizations

Abstract: Some observers, including many "doomsday" futurists, have contended that a pre dominant characteristic of future society will be extreme scarcity. Viewing this as sumption of extreme scarcity as plausible (though not necessarily most probable), this conjectural essay considers some of the possible effects of sustained scarcity, particu larly sharp declines in public spending and public employment, on public organization behavior. The focus is on the effects of scarcity on four types of strategic choices in pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…We can find additional confirmation of the model's general implication that organizational decline increases rigidity in a wide variety of studies, particularly those focusing on public sector organizations and universities. Researchers have suggested that organizational decline leads to an efficiency orientation (Cameron, 1983;D'Aveni, 1989b), an internal focus (Whetten, 1981), restricted domain definition (Bozeman & Slusher, 1979), reduced innovativeness (Cameron, , and increased workforce homogeneity (Greenhalgh, 1983). Scholars argue that these outcomes increase rigidity and reduce an organization's capacity to innovate in response to organizational decline.…”
Section: Necessity Is the Mother Of Rigiditymentioning
confidence: 99%
“…We can find additional confirmation of the model's general implication that organizational decline increases rigidity in a wide variety of studies, particularly those focusing on public sector organizations and universities. Researchers have suggested that organizational decline leads to an efficiency orientation (Cameron, 1983;D'Aveni, 1989b), an internal focus (Whetten, 1981), restricted domain definition (Bozeman & Slusher, 1979), reduced innovativeness (Cameron, , and increased workforce homogeneity (Greenhalgh, 1983). Scholars argue that these outcomes increase rigidity and reduce an organization's capacity to innovate in response to organizational decline.…”
Section: Necessity Is the Mother Of Rigiditymentioning
confidence: 99%
“…According to , the works published during this period show three theoretical foundations for organizational decline: the literature on organizational environment highlights the importance of organizations having control over critical environmental resources, represented by the works of Aldrich (1979); the literature on crisis management addresses the impact of environmental discontinuities in organizations, in the works of Starbuck et al (1978) and Smart and Vertinsky (1977); and the literature on the management of uncertainty, in the works of Thompson (1967). Other works regarding this factor were Whetten (1980) on organizational life-cycles, articles on retrenchment (Whetten, 1981), the definition of a typology of decline (Zammuto & Cameron, 1985) and the difference between decline and stagnation (Bozeman & Slusher, 1979).…”
Section: -2014mentioning
confidence: 99%
“…Bozeman and Slusher (1979) also found that public organizations dominated by the managerial subsystem were similarly insensitive to the external environment, heaping "dysfunction upon dysfunction," continually searching for solutions of the same or a similar type in a form of paralysis which left them unable to produce new technological solutions to the problem. Overall, the literature suggests that the institutional component within public organizations has to be represented in order to achieve effective public control (Gruber 1984), and that underrepresentation of the technical subsystem can be literally a recipe for disaster (Romzek and Dubnick 1987).…”
Section: The Impact Of Changing Management Typementioning
confidence: 99%